A study on organizational culture affecting Total Quality Management (TQM) implementation / Nur Atiqah Md Khamis, Nur Farahin Rahim, Shafika Suhada Kamaruddin - Md Khamis, Nur Atiqah; Rahim, Nur Farahin; Kamaruddin, Shafika Suhada (2014)
The first purpose of this research is to examine the relationship between organizational culture dimensions affecting total quality management implementation within organizations. The second proposed is to examine critical factors in organizational culture (individualism/collectivism, masculinity/femininity, power distances, long term/short term orientation and uncertainty avoidance) that contributes most to total quality management implementation within business organizations. This study was carried out at three business organizations that are Lembaga Tabung Haji Kota Bharu, Celcom Axiata Berhad Kuantan, and SME Corporation Kota Bharu. Researchers have use questionnaire as an instrument to collect data which is adapted from previous journal. It is based on the response of 235 employees as respondents. There are six variables that are used in this research consist five independent variables (individualism/collectivism, masculinity/femininity, power distances, long term/short term orientation and uncertainty avoidance) and dependent variable (total quality management). Researchers want to investigate the relationship between these variable. Research proved that three independent variables have significant influence to the total quality management. Research limitation is the results may not be generalized to represent all business organizations in Malaysia. There may be other variables related to organizational culture which were not included in this study and the research was conducted exclusively in English. This research will be useful to business organization in order to improve their total quality management implementation within business organizations.This research discuss about organizational culture affecting total quality management (TQM) implementation within business organizations.